PRINCIPALS' MANAGEMENT EFFORTS IN IMPROVING TEACHERS' PERFORMANCE AT JUNIOR HIGH SCHOOL - Musyafak, Ali (Jurnal Profesi Keguruan, 2024)
A headmaster is crucial in implementing the school's educational process. In organizational management, they play a role in formulating policies, implementing programs, and enhancing teacher capacity. This research is a qualitative study using a case study model. The subjects discussed are the Principal of MTs N 1 Pati and the teachers. This study aims to reveal the strategies used by the Principal to improve teacher quality. The results point out that the Principal undertakes several efforts, namely: 1) motivating teachers to continue learning and innovating, 2) providing the best facilities or infrastructure, 3) conducting regular supervision of teacher performance, and 4) organizing training, workshops, seminars, and focused discussions for teachers. These steps are highly effective as the teachers' performance improves.